Legal Implications of Unauthorized Distribution of Face Stickers in Digital Privacy: Implikasi Hukum dari Distribusi Stiker Wajah yang Tidak Sah dalam Privasi Digital - Prasetiantara, Rafi; Multazam, Mochammad Tanzil (Universitas Muhammadiyah Sidoarjo, 2024)
General Background: Technological advancements have significantly enhanced access to digital platforms, yet a substantial portion of the population remains uninformed about internet privacy and the responsible sharing of personal data. Specific Background: The Personal Data Protection Law outlines the obligations of data controllers to safeguard personal information, particularly regarding unauthorized data usage, such as the distribution of face stickers on social media. Knowledge Gap: Despite existing regulations, the legal implications of distributing face stickers without permission, particularly concerning copyright and privacy violations, are insufficiently explored in current literature. Aims: This study aims to identify and analyze the legal ramifications of unauthorized face sticker distribution, emphasizing the need for compliance with copyright and individual privacy laws. Results: Utilizing normative research methods with a statutory approach, this research evaluates relevant legal materials, including UU No. 27 Tahun 2022 and UU No. 28 Tahun 2014, to reveal the serious legal consequences for individuals engaging in unauthorized face sticker distribution. Novelty: The study's systematic interpretation of laws connects various legal frameworks, providing a comprehensive understanding of the interplay between privacy rights and copyright protections in the digital landscape. Implications: The findings underscore the necessity for enhanced public awareness regarding legal obligations surrounding copyright and individual privacy, aiming to foster responsible technology use and mitigate the risks of legal infractions in the digital age. Highlights: Data Controllers: Obligated to protect personal data from unauthorized access. Face Stickers: Legal issues arise from unauthorized distribution without consent. Public Understanding: Increase awareness of copyright and privacy regulations. Keywords: Personal Data Protection, Copyright, Internet Privacy, Face Stickers, Legal Implications